ANALYSIS OF EMR USER INTERFACE REQUIREMENT BY MEDICAL STUDENT - Mohd Khanapi , Abd Ghani; Nuur Farhana Shatilah Zakaria N.F.S, Zakaria (2014)
The aim of this study is to analyse user interface requirement for electronic medical record (EMR) system. This study is done through semi-structured interview with final year medical student. A participatory design approach was used to collect EMR user interface requirement from one of medical school in Malaysia. The scopes of analysis involve identifying the layout usage of user interface, navigation menu, navigation menu arrangement, user interface components and screen colour. The input collected from the study will be used to develop EMR user interface model.